Crop coefficient determination and evapotranspiration estimation of watermelon under water deficit in a cold and arid environment - Zhang, Hengjia; Wang, Zeyi; Yu, Shouchao; Teng, Anguo; Zhang, Changlong; Lei, Lian; Ba, Yuchun; Chen, Xietian (Frontiers in Plant Science, 2023)
To investigate the evapotranspiration and crop coefficient of oasis watermelon under water deficit (WD), mild (60–70% field capacity, FC) and moderate (50–60% FC) WD levels were set at the various growth stages of watermelon, including seedling stage (SS), vine stage (VS), flowering and fruiting stage (FS), expansion stage (ES), and maturity stage (MS), with adequate water supply (70–80% FC) during the entire growing season as a control. A two-year (2020-2021) field experiment was carried out in the Hexi oasis areas of China to explore the effect of WD on watermelon evapotranspiration characteristics and crop coefficient under sub-membrane drip irrigation. The results indicated that the daily reference crop evapotranspiration showed a sawtooth fluctuation which was extremely significantly and positively correlated with temperature, sunshine hours, and wind speed. The water consumption during the entire growing season of watermelon varied from 281–323 mm (2020) and 290–330 mm (2021), among which the phasic evapotranspiration valued the maximum during ES, accounting for 37.85% (2020) and 38.94% (2021) in total, followed in the order of VS, SS, MS, and FS. The evapotranspiration intensity of watermelon increased rapidly from SS to VS, reaching the maximum with 5.82 mm·d-1 at ES, after which it gradually decreased. The crop coefficients at SS, VS, FS, ES, and MS varied from 0.400 to 0.477, from 0.550 to 0.771, from 0.824 to 1.168, from 0.910 to 1.247, and from 0.541 to 0.803, respectively. Any period of WD reduced the crop coefficient and evapotranspiration intensity of watermelon at that stage. And then the relationship between LAI and crop coefficients can be characterized better by an exponential regression, thereby establishing a model for estimating the evapotranspiration of watermelon with a Nash efficiency coefficient of 0.9 or more. Hence, the water demand characteristics of oasis watermelon differ significantly during different growth stages, and reasonable irrigation and water control management measures need to be conducted in conjunction with the water requirements features of each growth stage. Also, this work aims to provide a theoretical basis for the irrigation management of watermelon under sub-membrane drip irrigation in desert oases of cold and arid environments.